Perception As A Moderating Variable Of The Influence Of Sharia Financial Literacy On The Decision To Become A BSI Customer - Rinna Ramadhan Ain Fitriah; Swadia Gandhi Mahardhika; Akbar Lufi Zulfikar; Nurfiza Widayati (Yayasan Inovasi Kemajuan Intelektual, 2025)
This study is a quantitative study with an explanatory approach, which uses previous research as the primary fuel to elaborate more deeply in this study and add new variations. The data used in this study are primary data that researchers obtained from 250 students throughout Indonesia. The data obtained was analyzed using the innovative PLS 4.0 analysis tool. The result of this article shows that the Sharia Financial Literacy variable can have a positive relationship direction and a significant influence on the decision to become a BSI customer. The P-values ​​in this article are positive and below the significance level of 0.05, namely 0.003. These results indicate that the Sharia Financial Literacy variable can improve students' financial conditions, intelligence, and so on, ultimately affecting the Decision To Become A BSI Customer. In the next row, the Perception variable can also moderate the influence of the Sharia Financial Literacy variable on the Decision To Become A BSI Customer because the P-values ​​are positive and below the significance level of 0.05, namely 0.000, more significant than the direct test, 0.003. Thus, it can be concluded that this article's first and second hypotheses can be accepted.